Ruthenium(VIII) Catalyzed Oxidation of Some Cyclic Alcohols by Sodium Periodate in Alkaline Medium - SRIVASTAVA, SHEILA; SINGH, SARIKA; SRIVASTAVA, PARUL (Asian Journal of Chemistry, 2010)
Kinetic investigations on ruthenium(VIII) catalyzed oxidation of cyclic alcohols (viz., cyclopentanol, cyclohexanol and cycloheptanol) by alkaline solution of sodium periodate in the presence of mercury(II) acetate as a scavenger have been made in the temperature range of 30-45ºC. The rate of oxidation shows first order kinetics with respect to sodium periodate and Ru(VIII) while order of the reaction is zero with respect to substrate and positive with respect to hydroxyl ions. Insignificant influence of mercury(II) acetate and ionic strength of the medium was observed. A suitable mechanism in conformity with the kinetic observations has been proposed and the thermodynamic parameters computed.